Advancing Universal Oral Health Coverage via Person-Centred Outcomes - Gustavo G. Nascimento; Eero Raittio; Vanessa Machado; Fábio R.M. Leite; João Botelho (Elsevier, 2023)
The World Health Organization member states proposed a comprehensive "Global Strategy on Oral Health," which includes achieving universal oral health coverage by 2030. Challenges and barriers, including persistent inequalities, will hamper the achievement of universal oral health coverage. In low- and middle-income countries, the oral health of a large proportion of the population has been neglected, increasing oral health inequalities. In high-income countries, some receive excessive dental treatment, whilst particularly those with higher needs receive too little dental care. Therefore, an analysis of individual countries' needs, encompassing the training of oral health professionals in a new philosophy of care and attention and the optimisation of the existing resources, is necessary. Distancing from a person-centred focus has prompted individual and societal issues, including under-/overdiagnosis and under-/overtreatment. The person-centred approach considers the perceptions, needs, preferences, and circumstances of individuals and populations. Patient-reported outcome measures, such as self-rated and -reported health, reflect an individual's overall perception of health and are designed to mediate human biology (ie, the disease) and psychology. The usage of patient-reported outcome measures in dentistry to place the individual at the centre of treatment is delayed compared to other areas. This paper discusses some challenges and potential solutions of patient-reported outcome measures in dentistry for achieving universal oral health coverage.